Memahami Hukum Perjanjian Islam: Teori, Asas, dan Praktek - Rohmah Maulidia (Justicia Islamica, 2008)
This study aims to understand the law of contract in Islam comprehensively, covering aspects of theory, legal principles, and their practice in modern life. The law of Islamic contract is based on the principles of justice, willingness (taradhi), and clarity ('adam al-jahalah) between the parties. This study uses a qualitative method with a literature study approach, examining classical fiqh literature, contemporary Islamic legal documents, and contract practices in Islamic economics. The results show that Islamic contract law has high flexibility as long as it does not contradict sharia principles. In addition, principles such as freedom of contract and the obligation to fulfill promises (al-'uqud musyahadah) remain relevant in the modern legal system. This study emphasizes that Islamic contract law can be a strong normative foundation for ethical and fair business contracts.